2007
DOI: 10.1007/s00586-007-0541-5
|View full text |Cite
|
Sign up to set email alerts
|

What comprises a good outcome in spinal surgery? A preliminary survey among spine surgeons of the SSE and European spine patients

Abstract: Standardized and validated self-administered outcome-instruments are broadly used in spinal surgery.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Effective scientific evaluation governed by reliable scientific principles is essential. 18,19 Thus, we fully agree with those [20][21][22][23][24][25][26][27] who recommend the use of multiple means of measurement that respect cultural, social, and personal differences present in the patients that we propose to evaluate, and it is in this manner that we developed this prospective study.…”
Section: Discussionsupporting
confidence: 82%
“…Effective scientific evaluation governed by reliable scientific principles is essential. 18,19 Thus, we fully agree with those [20][21][22][23][24][25][26][27] who recommend the use of multiple means of measurement that respect cultural, social, and personal differences present in the patients that we propose to evaluate, and it is in this manner that we developed this prospective study.…”
Section: Discussionsupporting
confidence: 82%
“…Because their mobility and activities of daily living tend to be affected, the fear of losing their independence is greater than that in younger individuals. 27 This stresses the importance of setting realistic expectations for the patients. Interestingly, a study by Gepstein et al 22 found that in patients older than 64 years, there was such a correlation between high expectations and satisfaction in those treated for lumbar spinal stenosis that preoperative expectations could be used to predict patient satisfaction.…”
Section: Clinical Outcomementioning
confidence: 99%
“…Incidence of lumbar spinal stenosis is increasing due to the aging population [25,26]. Lumbar stenosis is detected also more frequently these days, due to the better quality and availability of radiological imaging facilities.…”
Section: Discussionmentioning
confidence: 99%